Mechanism of muscle injury from eccentric exercise induced free radicals and protection with antioxidants - Klarod, Kultida; Surakul, Pornprom (Chulalongkorn Medical Journal, 2020)
Eccentric contraction exercise causes more muscle injury and damage than concentric exercise. The mechanism of muscle damage is divided into primary and secondary damages. One of the importance sources of secondary damage is derived from reactive oxygen species (ROS), which an increase of ROS results in the destruction of muscle tissue. Eccentric exercise is not only indicated adverse effect, but also suggested a positive effect with regular training. As a result of eccentric exercise promotes adaptation and prevention, thus some interventions should be taken into consideration for ameliorating negative effects. Antioxidant supplementation has been observed to be a method for relieving negative effect at the beginning of eccentric exercise. Antioxidant has been illustrated as molecules that control the adverse effect from ROS-induced muscle damage. An improved antioxidant level is believed to be a beneficial aspect against oxidative stress which develops from adaptation through exercise training. Previous studies observed the positive consequences of increased vitamin levels, however, several investigations have reported controversial results. In addition, enzymatic antioxidants are able to be controlled by effector cells that are induced, stimulated, and activated, which an increasing or decreasing of these antioxidants are still be disputed. Besides, the responsiveness of free radicals and antioxidants to eccentric exercise also depends on the intensity and duration of exercise.